Characteristics of Li‐Fraumeni syndrome in Japan: A review study by the special committee of JSHT. Issue 7 (17th May 2021) - Funato, Michinori; Tsunematsu, Yukiko; Yamazaki, Fumito; Tamura, Chieko; Kumamoto, Tadashi; Takagi, Masatoshi; Kato, Shunsuke; Sugimura, Haruhiko; Tamura, Kazuo
Abstract: Li‐Fraumeni syndrome (LFS) is a hereditary cancer predisposition syndrome, and the majority of patients with LFS have been identified with germline variants in the p53 tumor suppressor ( TP53 ) gene. In the past three decades, considerable case reports of TP53 germline variants have been published in Japan. To the best of our knowledge, there have been no large‐scale studies of Japanese patients with LFS. In this study, we aimed to identify Japanese patients with TP53 germline variants and to reveal the characteristics of LFS in Japan. We collected reported cases by reviewing the medical literature and cases diagnosed at the institutions of the authors. We identified 68 individuals from 48 families with TP53 germline pathogenic or likely pathogenic variants. Of the 48 families, 35 (72.9%) had missense variants, most of which were located within the DNA‐binding loop. A total of 128 tumors were identified in the 68 affected individuals. The 128 tumor sites were as follows: breast, 25; bones, 16; brain, 12; hematological, 11; soft tissues, 10; stomach, 10; lung, 10; colorectum, 10; adrenal gland, 9; liver, 4; and others, 11. Unique phenotype patterns of LFS were shown in Japan in comparison with those in a large national LFS cohort study in France. Above all, a higher frequency of patients with stomach cancer was observed in Japanese TP53 germline variant carriers. These results may provide useful information for the clinical management of LFS in Japan. Abstract : Comparing this study in Japan with a large national Li‐Fraumeni syndrome cohort study in France, the unique phenotype patterns of Li‐Fraumeni syndrome was shown in Japan. Especially, the higher frequency of patients with stomach cancer in Japanese TP53 germline variants carriers was shown.